REMAKING OF THE NEW STATE IN WATER MANAGEMENT - Rahmadi, R Y Gembong; Sahdan, Gregorius; Firdaus, Mohamad; Sulistiana, Utami; Wijaya, Junior Hendri; Etebom, John Monday (GOVERNABILITAS (Jurnal Ilmu Pemerintahan Semesta), 2024)
This study illustrates the dominance of the state through subdistrict governments and the private sector in managing water as a shared resource in the Special Region of Yogyakarta. The state's dominance in managing water resources, as a collectively owned resource, results in limited community access to water as a resource that should be enjoyed together. The need for waterfalls in DIY is very large every year, especially when entering the dry season. Girikerto's location at the foot of Mount Merapi means that the area has abundant water resources. However, the local community actually has limited access to water due to the cooperation between the district government and the private sector in dropping water into Gunungkidul Regency. The aim of this research is to illustrate how the state, through sub-district governments, can still provide local communities with access to utilize the water resources they need to meet their daily living needs. The results of this research show that the state, through the village government, has provided access to local communities to enjoy water.